Effect of Environmental Conditions on the Resistance of Damaged Composite Materials (Fracture and Structural Integrity, 2019)
The present paper proposes a strength model for unidirectional composites with Lin/Epoxy. The model assumes that, a central core of broken fibers flanked by unbroken fibers which are subject to stress concentrations from the broken fibers. The approach of the model consists of using a modified shear lag model to calculate the ineffective lengths and stress concentrations around fiber breaks. In this paper, we attempt to incorporate in the proposed model the unidirectional composite property variation with temperature and moisture in order to predict even composite strength degradation. Strength degradation is often seen as a result of changes in ineffective lengths at fiber breaks. Subsequently, damage to the material can be estimated at the micromechanical scale under the effect of temperature and humidity.
Keywords: Unidirectional composite; Broken fibers; Micromechanics; Composite Lin/Epoxy